Fabrication of polymer-based vertical comb drive using a double-side multiple partial exposure method - Chung, Junwei; Huang, Yuande; Hsu, Wensyang (My University, 2008)
A novel approach by using a double-side multi partial exposure (DoMPE) method to fabricate the polymer-based vertical comb drive with the thick photoresist AZ9260 (R) as the structural material is proposed. With the front-side partial exposure to define height of the fixed lower fingers and back-side partial exposure to create suspending space of the upper fingers, the staggering sets of fingers with a proper initial overlap and self-alignment are easily achieved without any additional sacrificial layer. The metal layer is finally deposited on the structural surface by sputtering for the suitable electrical conductivity to activate the polymer vertical comb drive (VCD). The operation model is performed by the theoretical analysis and FEM simulation, and the static deflection and dynamic response of the polymer VCDs are characterized finally. By comparing the analytical and experimental results, the feasibility on the fabrication of polymer VCD is verified with a measured rotation angle of 2.31 degrees under the driving voltage of 158.3V.